Answer to Question #231190 in Differential Equations for Randal Rodriguez

Question #231190

eliminate the arbitrary constant using any method

15.y\:=\:C_1e^{−3x}\:-2C_2e^{-3x}


1
Expert's answer
2021-09-07T02:07:04-0400
"y=C_1e^{-3x}-2C_2e^{-3x}"

"y=C_3e^{-3x}"

Dividing throughout by "e^{-3x}," we get


"ye^{3x}=C_3"

Differentiating with respect to "x," we get


"e^{3x}y'+3e^{3x}y=0"

Dividing throughout by "e^{3x}," we get


"y'+3y=0"




Need a fast expert's response?

Submit order

and get a quick answer at the best price

for any assignment or question with DETAILED EXPLANATIONS!

Comments

No comments. Be the first!

Leave a comment

LATEST TUTORIALS
New on Blog